1995
DOI: 10.1677/joe.0.1440555
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of growth hormone-releasing hexapeptide (GHRP-6) on growth hormone release are inhibited by central somatostatin action

Abstract: Growth hormone (GH) release is stimulated by a variety of synthetic secretagogues, of which growth hormone-releasing hexapeptide (GHRP-6) has been most thoroughly studied; it is thought to have actions at both pituitary and hypothalamic sites. To evaluate the central actions of this peptide, we have studied GH release in response to direct i.c.v. injections in anaesthetized guinea pigs. GHRP-6 (0.04-1 microgram) stimulated GH release > 10-fold 30-40 min after i.c.v. injection. The same GH response required > 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 0 publications
4
51
2
Order By: Relevance
“…Furthermore, somatostatin was found to inhibit GHRP-6-induced secretion of GH in vitro (Cheng et al 1989. Therefore, although the current study and that of Guillaume et al (1994) do not support a decrease in secretion of somatostatin into hypophysial-portal blood, this does not discount the possibility that GHRP-6 blocks the somatostatin inhibition of GHRH neurons in the arcuate nucleus (Fairhall et al 1995). It is possible, as Fairhall et al (1995) suggested, that GHRP-6 blocks somatostatin receptors, which, in turn, enables secretion of GHRH.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, somatostatin was found to inhibit GHRP-6-induced secretion of GH in vitro (Cheng et al 1989. Therefore, although the current study and that of Guillaume et al (1994) do not support a decrease in secretion of somatostatin into hypophysial-portal blood, this does not discount the possibility that GHRP-6 blocks the somatostatin inhibition of GHRH neurons in the arcuate nucleus (Fairhall et al 1995). It is possible, as Fairhall et al (1995) suggested, that GHRP-6 blocks somatostatin receptors, which, in turn, enables secretion of GHRH.…”
Section: Discussioncontrasting
confidence: 84%
“…Therefore, although the current study and that of Guillaume et al (1994) do not support a decrease in secretion of somatostatin into hypophysial-portal blood, this does not discount the possibility that GHRP-6 blocks the somatostatin inhibition of GHRH neurons in the arcuate nucleus (Fairhall et al 1995). It is possible, as Fairhall et al (1995) suggested, that GHRP-6 blocks somatostatin receptors, which, in turn, enables secretion of GHRH. Blockade of somatostatin receptors on GHRH neurons, rather than directly stimulating GHRH neurons does not account for increased expression of c-fos in the arcuate nucleus unless GHRP-6 activates neurons other than GHRH, which, in turn, stimulate secretion of GHRH.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This simplified view is justified for the present simulations, although it is known that flooding the hypothalamus with SRIF prior to ghrelin application will abolish the ghrelin effect (Fairhall et al 1995). This latter effect could easily be implemented using a SRIF threshold for the ghrelin-induced GHRH release.…”
Section: Ghrh Oscillationsmentioning
confidence: 98%
“…In combination with substances that inhibit or counteract somatostatin, e.g. ARG, pyridostigmine or GHS (25), GHRH becomes the most potent and reproducible stimulus of GH secretion; it explores the maximal secretory capacity of somatotroph cells that, in turn, reflects the appropriately normal function of hypothalamic network controlling GH synthesis and release. Provided that the peak GH response to these tests is referred to appropriate cut-off limits (!20 mg/l in childhood), they are as reliable as classical provocative tests to distinguish between normal and deficient GH secretory capacity.…”
Section: Diagnosis Of Ghd In Childhoodmentioning
confidence: 99%